1990
DOI: 10.1051/agro:19900601
|View full text |Cite
|
Sign up to set email alerts
|

Relation entre quelques caractères morphologiques et la sensibilité à la verse en végétation du maïs (Zea mays L)

Abstract: fig 5). These results emphasize the role of the roots of the upper internodes on stem stability. The date of appearance of these roots, and their mechanical properties, must also be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Although yield differences were not significant in this field experiment, ridging may improve yield potential under conditions where lodging and rootworm damage limit yields. Pellerin et al (1990) examined 12 maize hybrids with different root morphologies, and confirmed that development of FRat aboveground nodes (Nodes 6, 7, 8, and/or 9) is important in lodging resistance. During a severe lodging event, maize hybrids with roots at Node 6 had very little lodging, while hybrids with roots only up to Node 4 showed severe lodging.…”
Section: Field Experimentsmentioning
confidence: 75%
“…Although yield differences were not significant in this field experiment, ridging may improve yield potential under conditions where lodging and rootworm damage limit yields. Pellerin et al (1990) examined 12 maize hybrids with different root morphologies, and confirmed that development of FRat aboveground nodes (Nodes 6, 7, 8, and/or 9) is important in lodging resistance. During a severe lodging event, maize hybrids with roots at Node 6 had very little lodging, while hybrids with roots only up to Node 4 showed severe lodging.…”
Section: Field Experimentsmentioning
confidence: 75%
“…Regarding whole plant yield, the effects of GCA (general combining ability) were preponderant, and the ratio between the variance of SCA (specific combining ability) and that of GCA was smaller than for grain yield (eg, Dhillon et al, 1990a;Geiger et al, 1992;Barrière et al, 1993a (Hallauer, 1990 (Dubreuil et al, 1996), and pointing out the complementary management of lines to be used as progenitors in pedigree breeding. This could further be improved if these techniques were coupled with statistical methods allowing the identification of the source of genes to be used in reciprocal improvement of lines (Dudley, 1992) Variation in the anchoring quality of the roots was related to the variation in the susceptibility to root lodging of hybrids (Andrew and Solanki, 1966;Musich et al;1965;Pellerin et al, 1990;Hébert et al, 1990-92). The genetic variation regarding resistance to lodging occurred with a large variation of all traits related to the form and structure of the root system.…”
Section: Silage Maize Yield and Earlinessmentioning
confidence: 99%
“…On maize, nodal roots of upper phytomers also play an important role in stem stability (Pellerin et al, 1990). On maize, nodal roots of upper phytomers also play an important role in stem stability (Pellerin et al, 1990).…”
Section: E M O T E S -M a I N A R D And Pellerinmentioning
confidence: 99%